Evaluating employer branding from the perspective of bachelor degree SBM ITB a students by using the 4e model case study : PT Telkom Indonesia, tbk - Ginting, Monica Sry Bina Br; Welly, John (Journal of Business and Management, 2019)
Abstract. This study discusses more in depth about Employer Branding using the 4E approach (employee engagement, employee empowerment, employee education, employee equity). This research was conducted in one of the SOEâ€™s in Indonesia, namely PT Telkom Indonesia, Tbk. The purpose is to measure the degree of employer branding of PT Telkom Indonesia, Tbk by using the 4E Model approach and to evaluate matters relating to employer branding of PT Telkom Indonesia, Tbk. The survey was conducted to 134 respondents of Management SBM ITB students batch 2018 who were seen as external assessors (job seekers). Responses were collected using a questionnaire, which contained questions compiled based on 4E Models (employee engagement, employee empowerment, employee education, employee equity). In data analysis, there are two approaches carried out in this study, namely quantitative analysis and qualitative analysis. Based on quantitative analysis results are obtained; 4E Model has a high degree of employer branding with an average of 4.55-5.01 (in detail the highest average degree is employee equity of 5.01 and the lowest is employee empowerment on a scale of 4.55). While qualitative analysis is used to find out what things need to be evaluated, especially related to employer branding, the evaluation process is done by analyzing unsatisfactory answers (illustrated on a scale of 1-3) by respondents to the distributed questionnaire. Based on qualitative analysis, PT Telkom Indonesia, Tbk must increase its employer branding by actively conducting recruitment campaigns in various media, for example: Linked-In; providing various corporate promotion programs such as campus visits ; utilizing gamification-based on technology in training and recruitment processes, and raising the community awareness by actively posted company achievements in various media, both social and print.Â Keywords: Employer branding, 4E's Model, Evaluation, Qualitative Analysis, Quantitative Analysis, State â€“ owned Enterprises, Respondents